High-adsorption-capacity aluminum lithium adsorption film and preparation method thereof
By using cationic linear polymers in the lithium adsorption film and combining an aluminum-based precursor, an ion mass transfer channel is constructed, which solves the problems of low adsorption amount and difficult two-dimensional structure design of the existing lithium adsorption film, and achieves efficient lithium ion adsorption effect.
Patent Information
- Application Number
- CN202411838250.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-21
AI Technical Summary
During the adsorption process, the amount of adsorption of the precursor by polymer linear polymers decreases, and the adsorption film with two-dimensional structure is difficult to design, with a long mass transfer path, which affects the adsorption efficiency.
A cationic linear polymer is mixed with an aluminum-based precursor, and a high-adsorption aluminum-based lithium adsorption film is prepared through cast coating technology to construct an ion mass transfer channel between the polymer and the embedded precursor, and shorten the mass transfer path of lithium ions.
It significantly improves the adsorption amount and adsorption speed of the adsorption film, improves the mass transfer efficiency of lithium ions, and is suitable for lithium adsorption treatment of salt lake brine.
Smart Images

Figure CN119657093A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium adsorption, and specifically relates to an aluminum-based lithium adsorption film with a high adsorption capacity, and further discloses a preparation method thereof. Background Art
[0003] As a highly efficient lithium adsorption and separation material, lithium adsorption membrane has high specific surface area, pore volume, and pore size. The channel and efficiency of ion mass transfer of the material have a decisive influence on the adsorption amount of the precursor, thereby fundamentally improving the total adsorption after granulation. In the traditional process of lithium extraction from salt lake brine, the commonly used aluminum-based lithium adsorbent precursors must undergo technologies such as embedding and granulation hydrophilic modification to meet the requirements of industrial application. In this process, due to the embedding of the precursor by the selected high molecular linear polymer, the adsorption amount will inevitably decrease, resulting in its adsorption capacity being only about 1 / 5 of the precursor, seriously affecting its performance. Therefore, this field urgently needs to improve the performance of linear polymers, establish ion mass transfer channels between polymers and embedded precursors, so that lithium ions in brine can be quickly transferred to adsorption sites, thereby increasing the adsorption amount.
[0004] To address this industry pain point, the current solution in the industry is to optimize the hydrophilicity of the material, as well as the granulation and encapsulation processes, to improve the specific surface area, pore volume, pore size and other parameters and characteristics of the adsorbent, so that as many effective adsorption sites in the precursor as possible are exposed to the mass transfer channels in the adsorbent particles. However, it is ignored that the precursor embedded in the polymer loses its adsorption capacity due to its inability to contact with lithium ions.
[0005] For example, Chinese patent CN106622103B discloses a method of mixing inorganic active powder, polymer and organic solvent, extruding and granulating, and then heat-treating to volatilize the solvent to form lithium adsorbent particles. However, during the volatilization and drying process of the organic solvent, a dense layer is easily formed on the surface of the particles, and there is no obvious pore structure on the surface and inside of the adsorbent, which slows down the mass transfer rate between the adsorbent and the brine, affecting the adsorption amount and the adsorption and desorption rate.
[0006] For example, Chinese patent CN113509911B discloses a method of using a water-absorbent polymer as a carrier, adding a high loading amount of aluminum-based adsorbents such as lithium aluminum hydrotalcite, magnesium aluminum hydrotalcite, aluminum hydroxide, etc., and preparing it by secondary crosslinking. The polyhydroxy structure on the surface of the matrix effectively adsorbs the adsorbent particles and effectively reduces the dissolution rate, but the polyhydroxy structure in the skeleton can only improve the high water absorption of the material, and cannot bring about a high flux of cations, so it cannot improve the mass transfer rate of lithium ions in brine.
[0007] For example, Chinese patent CN106902774 discloses a method for granulating an aluminum salt adsorbent for extracting lithium from salt lake brine. The aluminum salt adsorbent is based on sodium alginate, and its particles are coated with a shell of polyethylene or polypropylene. The adsorbent particles prepared by this method have a porous structure and good water permeability. However, the adsorbent particles with natural polysaccharides such as sodium alginate as carriers have low strength and are easy to break. After multiple adsorption and desorption cycles, the cross-linking agent calcium ions are dissolved, and the adsorbent particles will swell.
[0008] For example, Chinese patent CN117753378A discloses a high-adsorption aluminum-based lithium adsorbent, which uses a mixed phase of an aluminum-based precursor and a cationic linear polymer as a reaction precursor, extrudes the material from the nozzle at high speed through extrusion pressure, enters a coagulation bath for rapid molding, and obtains an adsorbent product after crushing. However, the above-mentioned aluminum-based lithium adsorbent products are all three-dimensional structure products in a granular state, which are limited in practical applications due to factors such as volume. The two-dimensional structure products of adsorption membranes that are expected to be developed in this field are rarely reported because of their completely different structures, principles and performances from adsorbent products. This is mainly because the salt lake brine will travel along the internal winding channels in the three-dimensional structure adsorbent, with a long residence time, high operating pressure, and the internal channels are easily blocked, thereby inactivating the adsorption sites. In the two-dimensional structure adsorption membrane, since the membrane layer is extremely thin, the internal channels are mostly point-to-point through-hole structures, which will make the distance of each ion in the brine through the membrane extremely short, effectively reducing the system operating pressure. However, since the cross-linking structure of membrane materials in the microstructure is not as rich as that of adsorbent materials, there is a risk that the structure is more easily damaged. Therefore, compared with adsorbents with three-dimensional structures, the design of adsorption membranes with two-dimensional structures is more difficult, which is also the reason why adsorption membrane products are rarely used in the field of salt lake brine adsorption. Summary of the invention
[0009] To this end, the technical problem to be solved by the present invention is to provide an aluminum-based lithium adsorption membrane with a high adsorption capacity. The adsorption membrane system synthesizes a polymer material with ion mass transfer ability, that is, a cation mass transfer function, so that it has the ability to quickly transfer lithium ions to the embedded precursor adsorption sites, thereby achieving the effect of greatly improving the adsorption capacity of the adsorption membrane. The adsorption membrane has the advantages of fast adsorption speed and large adsorption capacity;
[0010] The second technical problem to be solved by the present invention is to provide a method for preparing the above-mentioned aluminum-based lithium adsorption film with high adsorption capacity.
[0011] In order to solve the above technical problems, the present invention provides a method for preparing an aluminum-based lithium adsorption film with a high adsorption capacity, comprising the following steps:
[0012] (1) preparing a reaction solution from a water-soluble lithium salt and a water-soluble aluminum salt, and adding a strong alkaline solution to react to obtain an aluminum precursor;
[0013] (2) dissolving the cationic linear polymer and the aluminum precursor in a solvent and mixing them to obtain a film-forming liquid;
[0014] (3) The film-forming liquid is applied to the surface of the substrate, and the film is solidified, dried, and flattened to obtain the film.
[0015] Specifically, in the method for preparing the aluminum-based lithium adsorption film with a high adsorption capacity, in the step (1), the molar ratio of the water-soluble lithium salt to the water-soluble aluminum salt is Al:Li=2:0.5-2.5, preferably 2:1-2;
[0016] Preferably, the water-soluble lithium salt includes one or a mixture of lithium chloride, lithium hydroxide, lithium oxalate, lithium sulfate or lithium nitrate;
[0017] Preferably, the water-soluble aluminum salt includes one or a mixture of aluminum chloride, aluminum sulfate, aluminum nitrate, aluminum acetate or basic aluminum carbonate.
[0018] Specifically, in the method for preparing the aluminum-based lithium adsorption film with a high adsorption capacity, in the step (1), the strong alkaline solution includes a NaOH solution;
[0019] Preferably, the concentration of the NaOH solution is 6-8 mol / l, preferably 6.5-7.5 mol / l;
[0020] Preferably, the end point of the dropwise addition of the NaOH solution and the reaction liquid is a pH value of 4-7, preferably a pH value of 5-7, and more preferably a pH value of 5.4-6.4.
[0021] Specifically, in the method for preparing the aluminum-based lithium adsorption film with a high adsorption capacity, in the step (1):
[0022] The reaction temperature is 50-100°C, preferably 60-80°C; and / or,
[0023] The stirring speed of the reaction step is 150-300 r / min, preferably 220-280 r / min; and / or,
[0024] The reaction liquid is added to the strong base solution at a rate of 5-40 ml / min, preferably 10-20 ml / min; and / or,
[0025] The step (1) also includes the step of collecting the reaction product and subjecting it to aging and drying to obtain the desired aluminum precursor;
[0026] Preferably, the aging step is performed for 30-240 min, preferably 120-180 min;
[0027] Preferably, the temperature of the drying step is 100-120°C, preferably 100-108°C.
[0028] Specifically, in the method for preparing the aluminum-based lithium adsorption membrane with a high adsorption capacity, in the step (2), the cationic linear polymer includes a mixture of one or more of polysulfonated styrene, sulfonated styrene-maleic anhydride copolymer, sulfonated polyacrylamide, chlorosulfonated polyethylene, and cationic polyacrylamide;
[0029] Preferably, the mass ratio of the cationic linear polymer to the aluminum precursor is 1:20-1, preferably 1:10-2.
[0030] Specifically, in the method for preparing the aluminum-based lithium adsorption film with a high adsorption capacity, in the step (2), the solvent includes one or a mixture of cyclohexanone, N,N-dimethylformamide, N,N-dimethylacetamide, dichloromethane, dichloroethane, chloroform, tetrachloromethane, dichloropropane, N-methylpyrrolidone, ethyl acetate, ethanol or water;
[0031] Preferably, the mass ratio of the solvent to the cationic linear polymer is 15-1:1, preferably 10-5:1.
[0032] Specifically, in the method for preparing the aluminum-based lithium adsorption film with a high adsorption capacity, in the step (3), the coating step includes tape casting;
[0033] Preferably, the parameters of the film casting step include: controlling the material viscosity to 300-2000 cP, preferably 300-1000 cP, controlling the casting thickness to 20-200 um, preferably 50-150 um, and controlling the walking speed to 0.1-2 m / min, preferably 0.5-1.5 m / min;
[0034] Preferably, the substrate includes non-woven fabric, woven mesh, porous membrane, etc., preferably non-woven fabric; the porous membrane is preferably made of PVC, PC, PVDF, etc.
[0035] Specifically, in the method for preparing the aluminum-based lithium adsorption film with a high adsorption capacity, in the step (3):
[0036] The coagulation bath of the coagulation step comprises at least one of ethanol, ethylene glycol, glycerol, butanone, cyclohexanone, dimethyl sulfoxide, methylal or water; and / or,
[0037] The temperature of the solidification step is 20-40°C; and / or,
[0038] The temperature of the drying step is 70-200°C; and / or,
[0039] The walking speed of the scraping step is 0.1-2m / min.
[0040] The invention also discloses an aluminum-based lithium adsorption film with high adsorption capacity prepared by the method.
[0041] The invention also discloses the application of the aluminum-based lithium adsorption membrane with high adsorption capacity in the field of lithium extraction from salt lake brine.
[0042] The high adsorption capacity aluminum-based lithium adsorption membrane of the present invention selects a linear polymer with cation mass transfer ability to further synthesize a polymer material with ion mass transfer ability. Its special cation mass transfer function enables it to have the advantage of quickly transferring lithium ions to the embedded precursor adsorption sites, and efficiently utilizes the embedded precursor adsorption sites. While maintaining the high specific surface area, pore volume and pore size of the adsorption membrane, it improves the internal ion mass transfer capacity of the material, greatly improves the adsorption capacity of the material, thereby achieving the effect of greatly improving the adsorption capacity of the adsorption membrane. The adsorption membrane product of the present invention has the advantages of fast adsorption speed and large adsorption capacity, and has obvious advantages in lithium extraction effect.
[0043] The high adsorption capacity aluminum-based lithium adsorption membrane of the present invention shortens the mass transfer path with maximum efficiency by converting the traditional three-dimensional granular lithium adsorbent into a two-dimensional planar lithium adsorption membrane, and constructs an ion mass transfer channel between the polymer and the embedded precursor, so that the lithium ions in the brine can be quickly transferred to the embedded adsorption sites, thereby increasing the adsorption capacity.
[0044] The aluminum-based lithium adsorption membrane with high adsorption capacity of the present invention has a special cation mass transfer function, which enables it to quickly transfer lithium ions to the embedded precursor adsorption sites, so that the embedded precursor can play its lithium ion adsorption and desorption functions, thereby increasing the adsorption sites. Compared with the traditional lithium adsorption membrane, the embedded precursor lacks lithium ion mass transfer channels, and at least half of the precursor cannot play the lithium ion adsorption and desorption effect, which can greatly increase the lithium adsorption capacity of the adsorption membrane.
[0045] The method for preparing the aluminum-based lithium adsorption film with high adsorption capacity of the present invention uses a mixed phase of an aluminum-based precursor and a cationic linear polymer as a reaction precursor, casts the material from a nozzle at high speed through a casting coating pressure, enters a coagulation bath for rapid molding, and obtains an adsorption film product after coating and scraping. The preparation method has the advantages of simple operation and strong processability. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein:
[0047] Figure 1-2 The internal SEM images of different positions of the adsorption film in Example 1; wherein, Figure 1This is a 20.0kv, 10.0k SEM electron microscope photo. Figure 2 These are 20.0kv and 30.0k SEM electron microscope photos. DETAILED DESCRIPTION
[0048] In the following embodiment of the present invention, a method for preparing an aluminum-based lithium adsorption film with a high adsorption capacity is provided, comprising the following steps:
[0049] (1) preparing a reaction liquid with a water-soluble lithium salt and a water-soluble aluminum salt, and adding a strong alkaline solution to react to obtain an aluminum precursor;
[0050] (2) dissolving the cationic linear polymer and the aluminum precursor in a solvent and mixing them to obtain a film-forming liquid;
[0051] (3) The film-forming liquid is applied to the surface of the substrate, and the film is solidified, dried, and flattened to obtain the film.
[0052] In some feasible implementation schemes, the preparation method of the aluminum-based precursor can refer to conventional synthesis methods in the art, such as the method described in the reference "Study on Preparation Process and Adsorption Performance of Aluminum Salt Lithium Adsorption Film" (Chengdu University of Technology, Master's thesis, Li Jie, Class of 2011).
[0053] As an exemplary embodiment, in the preparation process of the aluminum-based precursor, a water-soluble lithium salt and a water-soluble aluminum salt are selected to prepare a mixed solution, which is added dropwise into a strong alkaline solution under stirring to generate a white precipitate. After aging and drying, the aluminum-based precursor is obtained.
[0054] As an exemplary embodiment, the molar ratio of the water-soluble lithium salt to the water-soluble aluminum salt is Al:Li=2:0.5-2.5, preferably 2:1-2.
[0055] As an exemplary embodiment, the water-soluble lithium salt includes one or a mixture of lithium chloride, lithium hydroxide, lithium oxalate, lithium sulfate or lithium nitrate.
[0056] As an exemplary embodiment, the water-soluble aluminum salt includes one or a mixture of aluminum chloride, aluminum sulfate, aluminum nitrate, aluminum acetate or basic aluminum carbonate.
[0057] As an exemplary embodiment, the strong alkaline solution includes a NaOH solution; preferably, the concentration of the NaOH solution is 6-8 mol / l, preferably 6.5-7.5 mol / l.
[0058] As an exemplary embodiment, the end point of the dropwise addition of the NaOH solution and the reaction solution is a pH value of 4-7, preferably a pH value of 5-7, and more preferably a pH value of 5.4-6.4.
[0059] As an exemplary embodiment, the reaction temperature is 50-100°C, preferably 60-80°C.
[0060] As an exemplary embodiment, the stirring speed of the reaction step is 150-300 r / min, preferably 220-280 r / min.
[0061] As an exemplary embodiment, the addition rate of the reaction liquid to the strong alkaline solution is 5-40 ml / min, preferably 10-20 ml / min.
[0062] As an exemplary embodiment, the step (1) also includes the step of collecting the reaction products and subjecting them to aging and drying to obtain the desired aluminum precursor; for example, the aging step is performed for 30-240 minutes, preferably 120-180 minutes; for example, the drying step is performed at a temperature of 100-120°C, preferably 100-108°C.
[0063] As an exemplary embodiment, the adsorption capacity of the aluminum precursor prepared under the process conditions of the present invention can reach 2-5 mg / g.
[0064] As an exemplary embodiment, during the preparation of the film-forming liquid, the cationic linear polymer is dissolved in a solvent, and the aluminum-based precursor and the cationic linear polymer are evenly mixed to obtain the desired film-forming liquid.
[0065] As an exemplary embodiment, the cationic linear polymer includes a mixture of one or more of polysulfonated styrene, sulfonated styrene-maleic anhydride copolymer, sulfonated polyacrylamide, chlorosulfonated polyethylene, and cationic polyacrylamide.
[0066] As an exemplary embodiment, the mass ratio of the cationic linear polymer to the aluminum-based precursor is 1:20-1, preferably 1:10-2.
[0067] As an exemplary embodiment, the solvent includes one or a mixture of cyclohexanone, N,N-dimethylformamide, N,N-dimethylacetamide, dichloromethane, dichloroethane, chloroform, tetrachloromethane, dichloropropane, N-methylpyrrolidone, ethyl acetate, ethanol or water.
[0068] As an exemplary embodiment, the mass ratio of the solvent to the cationic linear polymer is 15-1:1, preferably 10-5:1.
[0069] As an exemplary embodiment, during the film forming and curing process, the film forming liquid is added into a casting coating machine and evenly coated on the non-woven fabric. After casting, it enters a coagulation bath, the temperature is maintained between 20-40°C, and the product is coagulated and dried, and then coated and scraped to obtain a finished adsorption film.
[0070] As an exemplary embodiment, the parameters of the casting coating step include: material viscosity 300-2000 cP, preferably 300-1000 cP, casting thickness 20-200 um, preferably 50-150 um, walking speed 0.1-2 m / min, preferably 0.5-1.5 m / min.
[0071] As an exemplary embodiment, the substrate includes non-woven fabric, woven mesh, porous membrane (such as PVC, PC, PVDF and the like).
[0072] As an exemplary embodiment, the coagulation bath of the coagulation step includes at least one of ethanol, ethylene glycol, glycerol, butanone, cyclohexanone, dimethyl sulfoxide, methylal, or water.
[0073] As an exemplary embodiment, the temperature of the drying step is 70-200°C.
[0074] As an exemplary embodiment, the walking speed of the scraping step is 0.1-2 m / min.
[0075] In order to have a deeper understanding of the present invention, the preferred experimental scheme of the present invention is described below in conjunction with examples to further illustrate the characteristics and advantages of the present invention. Any changes or modifications that do not deviate from the spirit of the present invention can be understood by those skilled in the art. The scope of protection of the present invention is determined by the scope of the claims.
[0076] In the following examples of the present invention, the raw materials, reagents, etc. used without indicating the manufacturer are all conventional products that can be purchased commercially. As an example of the raw materials used, the information involved is as follows:
[0077] Polysulfonated styrene was purchased from Shandong Jinyuan New Materials;
[0078] Sulfonated styrene-maleic anhydride copolymer was purchased from Beijing Zhongke Xinyuan;
[0079] Sulfonated polyacrylamide and cationic polyacrylamide were purchased from BASF;
[0080] Chlorosulfonated polyethylene was purchased from Jilin Petrochemical.
[0081] Example 1
[0082] Prepare an aqueous solution containing 2 mol / l aluminum chloride and 1.0 mol / L lithium chloride in a reaction bottle, prepare a 7 mol / L NaOH aqueous solution in another reaction bottle, and add the above aluminum and lithium aqueous solutions to the NaOH aqueous solution at a speed of 15 ml / min. At this time, the stirring speed of the NaOH reaction bottle is controlled at 240 r / min, and an online pH meter is inserted for real-time monitoring to control the titration endpoint to pH = 6.4. After heating the reaction bottle to 60°C and aging for 180 minutes, filter the material and put it into an oven at 108°C for drying to obtain an aluminum precursor, and its static lithium adsorption capacity is measured to be 4.5 mg / g for standby use.
[0083] Polysulfonated styrene was selected as the high molecular linear polymer, and N,N-dimethylformamide was selected as the solvent for mixing, with a solid-liquid mass ratio of 1:10, and mixed and dissolved with the polysulfonated styrene polymer. A precursor of 10 times the mass of the polysulfonated styrene was added thereto and mixed evenly to obtain a film-forming liquid, and its material viscosity was measured to be 550 cP.
[0084] The above film-forming liquid was added into the casting coating machine, the casting thickness was set to 100 μm, the walking speed was set to 1 m / min, and after coating and forming, it entered the coagulation bath, the coagulation bath was butanone, and the temperature was maintained at about 30°C. After the product was coagulated and vacuum dried at 100°C for 24 hours, it was coated and scraped to obtain the finished adsorption film.
[0085] Example 2
[0086] Prepare an aqueous solution containing 1.8 mol / L aluminum chloride and 1.8 mol / L lithium chloride in a reaction bottle, prepare a 6.5 mol / L NaOH aqueous solution in another reaction bottle, and add the aluminum and lithium aqueous solutions to the NaOH aqueous solution at a speed of 10 ml / min. At this time, the stirring speed of the NaOH reaction bottle is controlled at 220 r / min, and an online pH meter is inserted for real-time monitoring to control the titration endpoint to pH = 5.4. After heating the reaction bottle to 80°C and aging for 120 minutes, filter the material and put it into an oven at 100°C for drying to obtain an aluminum precursor, and its static lithium adsorption capacity is measured to be 3.8 mg / g for standby use.
[0087] Sulfonated styrene-maleic anhydride copolymer was selected as the high molecular linear polymer, and water was selected as the solvent for mixing, with the solid-liquid mass ratio of 1:5, and mixed and dissolved with the sulfonated styrene-maleic anhydride copolymer polymer. An aluminum precursor of 10 times the mass of the sulfonated styrene-maleic anhydride copolymer was added thereto, and a film-forming liquid was obtained after uniform mixing. The viscosity of the liquid was measured to be 350cP.
[0088] The film-forming liquid is added into a cast coating machine, the casting thickness is set to 100 μm, the walking speed is set to 0.5 m / min, and after internal coating and forming, it enters into a coagulation bath, the coagulation bath is N, N-dimethylacetamide, and the temperature is maintained at about 20°C. After the product is coagulated and vacuum dried at 100°C for 24 hours, it is coated and scraped to obtain a finished adsorption film.
[0089] Example 3
[0090] Prepare 2mol / L aluminum chloride and 2.5mol / L lithium chloride aqueous solutions in a reaction bottle, prepare 7.5mol / L NaOH aqueous solution in another reaction bottle, and add aluminum and lithium aqueous solutions to the NaOH aqueous solution at a speed of 20ml / min. At this time, the stirring speed of the NaOH reaction bottle is controlled at 280r / min, and an online pH meter is inserted for real-time monitoring to control the titration endpoint to pH = 6.2. After heating the reaction bottle to 60°C and aging for 160min, filter the material and put it into an oven at 100°C for drying to obtain an aluminum precursor, and its static lithium adsorption capacity is measured to be 4.2mg / g for standby use.
[0091] Chlorosulfonated polyethylene was selected as the high molecular linear polymer, and ethylene dichloride was selected as the solvent for mixing, with a solid-liquid mass ratio of 1:6, and mixed and dissolved with the chlorosulfonated polyethylene polymer. A precursor of 4 times the mass of the chlorosulfonated polyethylene was added thereto and mixed evenly to obtain a film-forming liquid, and the viscosity of the liquid was measured to be 780 cP.
[0092] The film-forming liquid was added to the casting coating machine, the casting thickness was set to 50 μm, the walking speed was set to 2 m / min, and after the internal coating was formed, it entered the coagulation bath, the coagulation bath was ethanol, and the temperature was maintained at about 40° C. The product was coagulated and vacuum dried at 70° C. for 24 hours, and then coated and scraped to obtain the finished adsorption film.
[0093] Example 4
[0094] Prepare 2mol / L aluminum chloride and 1.5mol / L lithium chloride aqueous solution in a reaction bottle, prepare 7.5mol / L NaOH aqueous solution in another reaction bottle, add aluminum and lithium aqueous solution to NaOH aqueous solution at a speed of 20ml / min, at this time, the stirring speed of the NaOH reaction bottle is controlled at 280r / min, and insert an online pH meter for real-time monitoring, and control the titration end point to pH = 4.6. After heating the reaction bottle to 60℃ and aging for 160min, filter the material and put it into an oven at 100℃ for drying to obtain an aluminum precursor, and its static lithium adsorption capacity is measured to be 4.8mg / g, which is ready for use.
[0095] Sulfonated polyacrylamide was selected as the high molecular linear polymer, and water was selected as the solvent for mixing, with the solid-liquid mass ratio of 1:8, and mixed and dissolved with the sulfonated polyacrylamide polymer. 8 times the mass part of the precursor of the sulfonated polyacrylamide was added thereto, and after mixing evenly, a film-forming liquid was obtained, and the viscosity of the liquid was measured to be 1400cP.
[0096] The film-forming liquid was added to the casting coating machine, the casting thickness was set to 20 μm, the walking speed was set to 2 m / min, and after the inner coating was formed, it entered the coagulation bath, the coagulation bath was acetone, and the temperature was maintained at about 30° C. The product was coagulated, vacuum dried at 40° C. for 24 hours, and then coated and scraped to obtain the finished adsorption film.
[0097] Example 5
[0098] Prepare 2mol / L aluminum chloride and 0.6mol / L lithium chloride aqueous solution in a reaction bottle, prepare 7.5mol / L NaOH aqueous solution in another reaction bottle, add aluminum and lithium aqueous solution to NaOH aqueous solution at a speed of 20ml / min, at this time, the stirring speed of the NaOH reaction bottle is controlled at 280r / min, and insert an online pH meter for real-time monitoring, and control the titration endpoint to pH = 4.4. After heating the reaction bottle to 60℃ and aging for 160min, filter the material and put it into an oven at 100℃ to dry, and obtain an aluminum precursor. The static lithium adsorption capacity is measured to be 2.8mg / g, and it is ready for use.
[0099] Cationic polyacrylamide was selected as the high molecular linear polymer, and water was selected as the solvent for mixing, with the solid-liquid mass ratio of 1:10, mixed and dissolved with the cationic polyacrylamide polymer, and 2 times the mass part of the precursor of the cationic polyacrylamide polymer was added thereto, and after mixing evenly, a film-forming liquid was obtained, and the viscosity of the liquid was measured to be 1200cP.
[0100] The film-forming liquid was added to the casting coating machine, the casting thickness was set to 200 μm, the walking speed was set to 0.1 m / min, and after the inner coating was formed, it entered the coagulation bath, the coagulation bath was acetone, and the temperature was maintained at about 30° C. The product was coagulated and vacuum dried at 70° C. for 24 hours, and then coated and scraped to obtain the finished adsorption film.
[0101] Comparative Example 1
[0102] Prepare 2mol / L aluminum chloride and 1.2mol / L lithium chloride aqueous solution in a reaction bottle, prepare 7mol / L NaOH aqueous solution in another reaction bottle, add aluminum and lithium aqueous solution to NaOH aqueous solution at a speed of 15ml / min, at this time, the stirring speed of NaOH reaction bottle is controlled at 240r / min, and insert an online pH meter for real-time monitoring, and control the titration end point to pH = 4.4. Heat the reaction bottle to 60℃ and keep it warm for 180min, filter the material and put it into an oven at 108℃ for drying, and set aside.
[0103] Polyvinyl chloride is selected as a high molecular linear polymer, and N,N-dimethylformamide is selected as a solvent for mixing. The solid-liquid mass ratio is 1:10, and it is mixed and dissolved with polyvinyl chloride. A precursor of 10 times the mass of polyvinyl chloride is added thereto, and after mixing evenly, a film-forming liquid is obtained, and the viscosity of the liquid is 2000cP.
[0104] The film-forming liquid was added to the casting coating machine, the casting thickness was set to 100 μm, the walking speed was set to 2 m / min, and after the inner coating was formed, it entered the coagulation bath, the coagulation bath was water, and the temperature was maintained between 20-40° C. After the product was coagulated and vacuum dried at 100° C. for 24 hours, the adsorption film product was obtained, but it was peeled off from the base film and could not be used.
[0105] Comparative Example 2
[0106] This comparative example scheme prepares the adsorption membrane product according to the scheme of Example 1 in Chinese patent CN108854996A.
[0107] Preparation of aluminum hydroxide: prepare an aqueous solution containing 2 mol / L aluminum nitrate nonahydrate and 1 mol / L lithium chloride, add urea for reaction, the molar ratio of urea to aluminum nitrate is 8:1, the reaction time is 120 min, and the reaction temperature is 20°C. After the reaction is completed, the obtained gel is centrifuged and washed with deionized water, and then centrifuged to obtain lithium-embedded aluminum hydroxide gel.
[0108] Modification of aluminum hydroxide: Mix the lithium-embedded aluminum hydroxide gel with an ethanol aqueous solution, and then add 5wt% γ-(methacryloyloxy)propyltrimethoxysilane ethanol solution to react. The weight ratio of the lithium-embedded aluminum hydroxide gel, the ethanol aqueous solution, and the ethanol solution of the silane coupling agent is 1:8:5. The reaction time is 120 minutes and the reaction temperature is 25°C. After the reaction is completed, the product is separated by centrifugation and washed with deionized water. After centrifugation and vacuum drying, modified aluminum hydroxide is obtained.
[0109] Load forming of adsorption film: by weight, add 0.2 parts of initiator dibenzoyl peroxide to 110 parts of deionized water, and heat to 40°C, then add 10 parts of modified aluminum hydroxide, 6 parts of styrene, 4 parts of cross-linking agent divinylbenzene, 14 parts of pore-forming agent toluene, 1.5 parts of hydroxyethyl methacrylate, 0.5 parts of dispersant SPAN-80 in an inert gas, and disperse evenly at high speed, then heat to react, react at 70°C for 120 minutes, centrifuge the product, wash with ethanol and vacuum dry to obtain a load-formed adsorption film.
[0110] Experimental example
[0111] 1. Static adsorption of adsorption film
[0112] This experimental example adopts the static adsorption detection method of the adsorption film for the performance detection process of the adsorption film. The specific method is as follows: use anhydrous lithium chloride reagent and prepare an adsorption mother solution with a lithium concentration of 307ppm with pure water for standby use. Weigh 0.2g of adsorption film in a 250ml conical flask, add 50ml of adsorption mother solution, seal it and put it into a constant temperature water bath shaker. The water temperature of the shaker is controlled at 40℃, the speed is 120r / min, and the adsorption is carried out for 12h. After the reaction is completed, take the adsorption mother solution and the supernatant in the conical flask, and use an ICP analyzer to detect the lithium ion concentration in the solution. The difference between the two is the adsorption amount of the lithium adsorption film.
[0113] The calculation formula is as follows:
[0114]
[0115] The moisture content of the adsorption film was detected by Mettler rapid moisture analyzer HC103.
[0116] In this experimental example, the performance test structure of the adsorption film products prepared in the above Examples 1-5 and Comparative Examples 1-2 is shown in Table 1 below.
[0117] Table 1 Results of static adsorption test of adsorption film samples by brine
[0118] serial number Brine Li content mg / L Unit adsorption capacity mg / ㎡ Example 1 307.2 25.21 Example 2 307.2 18.47 Example 3 307.2 15.28 Example 4 307.2 13.52 Example 5 307.2 10.37 Comparative Example 1 307.2 not available Comparative Example 2 307.2 5.57
[0119] It can be seen that the aluminum-based lithium adsorption membrane of the present invention not only has a fast adsorption speed and a large adsorption capacity, but also has obvious application advantages and can be applied to the lithium adsorption treatment of salt lake brine.
[0120] Furthermore, the aluminum-based lithium adsorption membrane of the present invention can form an adsorption membrane product capable of adsorbing lithium, and the entire adsorption membrane product has good applicability.
[0121] In the investigation of the long-term stability of the adsorption film, the adsorption film products prepared in Examples 1-3 have very ideal characteristics such as stability and durability of the adsorption film, and have more significant advantages than the adsorption film products in Examples 4-5.
[0122] 2. Product appearance
[0123] Take the adsorption film prepared in Example 1 above, and the SEM images of different positions inside the adsorption film are shown in the attached figure. Figure 1-2 As shown in Figure 2, it can be seen that the permeable channels formed by the adsorption membrane are more conducive to the passage of the medium.
[0124] It can be seen that the high-adsorption aluminum-based lithium adsorption membrane of the present invention shortens the mass transfer path with maximum efficiency by converting the traditional three-dimensional granular lithium adsorbent into a two-dimensional planar lithium adsorption membrane, and by constructing an ion mass transfer channel between the polymer and the embedded precursor, the lithium ions in the brine can be quickly transferred to the embedded adsorption sites, thereby increasing the adsorption capacity.
[0125] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A method for preparing an aluminum-based lithium adsorption film with a high adsorption capacity, characterized in that: The steps include: (1) preparing a reaction liquid with a water-soluble lithium salt and a water-soluble aluminum salt, and adding a strong alkaline solution to react to obtain an aluminum precursor; (2) dissolving the cationic linear polymer and the aluminum precursor in a solvent and mixing them to obtain a film-forming liquid; (3) The film-forming liquid is applied to the surface of the substrate, and the film is solidified, dried, and flattened to obtain the film.
2. The method for preparing the aluminum-based lithium adsorption film with high adsorption capacity according to claim 1, characterized in that: In the step (1), the molar ratio of the water-soluble lithium salt to the water-soluble aluminum salt is Al:Li=2:0.5-2.5, preferably 2:1-2; Preferably, the water-soluble lithium salt includes one or a mixture of lithium chloride, lithium hydroxide, lithium oxalate, lithium sulfate or lithium nitrate; Preferably, the water-soluble aluminum salt includes one or a mixture of aluminum chloride, aluminum sulfate, aluminum nitrate, aluminum acetate or basic aluminum carbonate.
3. The method for preparing the aluminum-based lithium adsorption film with high adsorption capacity according to claim 1 or 2, characterized in that: In the step (1), the strong alkaline solution includes a NaOH solution; Preferably, the concentration of the NaOH solution is 6-8 mol / l, preferably 6.5-7.5 mol / l; Preferably, the end point of the dropwise addition of the NaOH solution and the reaction liquid is a pH value of 4-7, preferably a pH value of 5-7, and more preferably a pH value of 5.4-6.
4.
4. The method for preparing the aluminum-based lithium adsorption film with high adsorption capacity according to any one of claims 1 to 3, characterized in that: In the step (1): The reaction temperature is 50-100°C, preferably 60-80°C; and / or, The stirring speed of the reaction step is 150-300 r / min, preferably 220-280 r / min; and / or, The reaction liquid is added to the strong base solution at a rate of 5-40 ml / min, preferably 10-20 ml / min; and / or, The step (1) also includes the step of collecting the reaction product and subjecting it to aging and drying to obtain the desired aluminum precursor; Preferably, the aging step is performed for 30-240 min, preferably 120-180 min; Preferably, the temperature of the drying step is 100-120°C, preferably 100-108°C.
5. The method for preparing the aluminum-based lithium adsorption film with high adsorption capacity according to any one of claims 1 to 4, characterized in that: In the step (2), the cationic linear polymer includes a mixture of one or more of polysulfonated styrene, sulfonated styrene-maleic anhydride copolymer, sulfonated polyacrylamide, chlorosulfonated polyethylene, and cationic polyacrylamide; Preferably, the mass ratio of the cationic linear polymer to the aluminum precursor is 1:20-1, preferably 1:10-2.
6. The method for preparing the aluminum-based lithium adsorption film with high adsorption capacity according to any one of claims 1 to 5, characterized in that: In the step (2), the solvent includes one or a mixture of cyclohexanone, N,N-dimethylformamide, N,N-dimethylacetamide, dichloromethane, dichloroethane, chloroform, tetrachloromethane, dichloropropane, N-methylpyrrolidone, ethyl acetate, ethanol or water; Preferably, the mass ratio of the solvent to the cationic linear polymer is 15-1:1, preferably 10-5:
1.
7. The method for preparing the aluminum-based lithium adsorption film with high adsorption capacity according to any one of claims 1 to 6, characterized in that: In the step (3), the coating step includes casting coating; Preferably, the parameters of the film casting step include: controlling the material viscosity to 300-2000 cP, the casting thickness to 20-200 um, and controlling the walking speed to 0.1-2 m / min; Preferably, the substrate comprises nonwoven fabric, woven mesh or porous membrane.
8. The method for preparing the aluminum-based lithium adsorption film with high adsorption capacity according to any one of claims 1 to 7, characterized in that: In the step (3): The coagulation bath of the coagulation step comprises at least one of ethanol, ethylene glycol, glycerol, butanone, cyclohexanone, dimethyl sulfoxide, methylal or water; and / or, The temperature of the solidification step is 20-40°C; and / or, The temperature of the drying step is 70-200°C; and / or, The walking speed of the scraping step is 0.1-2m / min.
9. An aluminum-based lithium adsorption film with high adsorption capacity prepared by the method according to any one of claims 1 to 8.
10. Application of the aluminum-based lithium adsorption membrane with high adsorption capacity as claimed in claim 9 in the field of lithium extraction from salt lake brine.
Citation Information
Patent Citations
A method for preparing lithium-ion enrichment materials for extracting lithium from lithium-containing brine.
CN106622103B
Aluminum salt adsorbent and application thereof in extraction of lithium in salt lake brine
CN108854996A
A method for preparing aluminum-based adsorbent particles for liquid lithium resource extraction
CN113509911B
Preparation method of aluminum lithium adsorbent with high adsorption capacity
CN117753378A